Tingkat Stres Dan Perawatan Diri (Self-Care) Pada Klien Diabetes Melitus Tipe 2 Di Poli Penyakit Dalam BLUD RSUD Dr. Doris Sylvanus - Natalansyah Natalansyah; Wulandari Wulandari; Barto Mansyah (Jurnal Surya Medika (JSM), 2020)
The International Diabetes Federation (IDF) estimates the number of DM increases in Indonesia from 9.1 million in 2014 to 14.1 million in 2035. Type 2 diabetes is the most common type. Diabetes is a group of metabolic diseases characterized by hyperglycemia due to defects in insulin secretion, insulin action, or a combination. Diabetes mellitus can cause clinical changes in diabetics. The purpose of this study was to study the relationship of stress levels with self-care on type 2 DM clients in BLUD Internal Medicine dr. Doris Sylvanus. This research method uses a cross-sectional study design, with a purposive sampling technique, the number of samples in this study were 35 respondents, collecting data using a Diabetes Self-Care Activity Summary questionnaire (SDSCA and Diabetes Disorders Scale (DSS) and analyzed using the chi-square test The results of this study indicate that of the 20 respondents who were severely stressed 18 respondents were not good in self-care and of the 15 respondents who increased mild stress 10 respondents were able to perform self-care well. = 0.001, where the p-value <α (α = 0 05) It can be concluded that there is a significant relationship between stress levels and self-care where the higher the stress level, the lower the self-care treatment.